AN APPROACH FOR CRITICAL EVALUATION OF EXAMINATION QUESTIONS IN AN ENGINEERING FACULTY USING THE CLASSICAL BLOOM TAXONOMY (Nigerian Journal of Technology, 2018)
Ideally, teaching curricula are designed to exude some learning behavioural outcomes in students. When students are examined through oral, practical and or theoretical evaluation schemes in examinations, the primary objective is to measure the relative extent to which students can exude the desired behavioural outcomes. Thus it is important that appropriate means and expressions are employed in assessment to measure learning. Based on an average-occurrence-rating scale, a set of Action verbs of the classical Bloom’s taxonomy were used in this study in assessing the level of learning outcomes required in each of 21 Engineering Core Course examination-questions used. Rates were computed for Knowledge, Comprehension, Application, Analysis, Synthesis and Evaluation levels of the Bloom’s Taxonomy. Marginalized One-Factor Statistical experiments and randomized two-factor Statistical experiments were designed using the rates computed. Analysis of Variance (ANOVA) technique was used to test within- and between-treatments variations of the differences of means for the six Bloom’s taxonomy levels using hypotheses at 0.05 levels of significance for each of the experimental design scenarios. Analyzed results show significant differences in course ratings at different Bloom taxonomy levels and significances in differences in ratings of the taxonomy for different courses. Group tests of hypotheses on differences of mean-ratings for the courses show significance. The study brings to light the need for examiners in these courses to put more effort in upper levels of behavioural outcomes especially on Synthesis and Evaluation which are germane for training of good Engineers. http://dx.doi.org/10.4314/njt.v37i4.28